Development of Technical Drawing Module Based On Projection and Sectional Views Equipped with Lego Block Assembly Media Assistance - Agung Prijo Budijono; Wahyu Dwi Kurniawan; Arda Widyatama (NAROTAMA UNIVERSITY, Indonesia, 2019)
. This research is motivated by the lack of practical learning media in the discussion of projections and pieces in the learning process of technical drawing courses. Referring to the discussion, the researcher made a module